Detection and prevention for SQL injection attacks in stored procedures using real time web application - Salih Ali, Nabeel (2015)
At present, web applications have been used for most of our activities in our life. Web applications are affected by the attacks of SQL injection. SQL injection is a prevalent technique that attackers appoint to impose the database in the most of web applications, by manipulate the SQL queries that send to RDBMS. Hence, change the behavior of the application. Stored procedures SQL injection attack is one of the serious attacks that posed database threats in the underlying database that underlie web applications. Whereas, the attack can be crafted to execute stored procedures that provided by a particular database, encompasses procedures that deal with the operating system. In this research, three major objectives can be organized to direct the work study are: Firstly, to investigate the attacks of SQL injection, and study what has been done to detect and prevent SQLIA in stored procedures in order to, eliminate the lack of their approaches and highlight their weakness, secondly, to identify the various obstacles and factors that would be encountered will be led to be successful to build an appropriate defensive approach to detect and prevent SQLIAs, and the third objective is, to develop WASP tool to build a real-time web application tool (RT-WASP) to detect the SQLIAs, and propose a suitable protective approach to prevent stored procedures SQLIAs. Our methodology encompassed, four phases, primary study or investigation phase, modeling phase, development and proposing phase, evaluations and discussion phase. Investigation phase will study current approaches to counter SQLIAs. Background study, highlight problems and weakness in order to address the gap in detection and prevention SQLIA domain. In modeling phase, evaluate the performance of the existing techniques to identify the factors that would be encountered will be led to get better and efficient results in our work study. In developing and proposing phase, a suitable tool will be developed, and effective preventive approach will be proposed. Evaluations and discussion phase will take a place in order to finalize our work research. The main contributions of this research study are: First, Summarized and analysis of a detailed review of various SQLI attacks and investigation of previous approaches that detected and prevented these attacks in Web applications. Second, developed WASP tool that has been proposed by Halfond.2008 to detect the attacks of SQLI in real-time web applications. Third, proposed a protective approach that includes three preventive mechanisms that are: parameterized stored procedures, customized error messages, and encryption stored procedures in the SQL server. In order to, prevent the danger of SQLIA in stored procedures, and the last contribution is, conducted a comparison analysis of the developed technique and proposed protective approach based on the evaluations respect to efficiency and effectiveness of the technique, and effectiveness of the proposed protective approach. RT-WASP was efficient due to able to stop all SQLIAs and did not generate any false negative, a few false positive values in the results, and pose, low overhead and minimal deploy requirements. Whilst, our protective approach was effectiveness due to, capable to prevent the attacks of stored procedures SQLIAs. Finally, identify and focus on the future scope.